A Note on “A One-sector Neoclassical Growth Model with Endogenous Retirement”: Existence of Multiple Steady States - Liutang Gong; Nianqing Liu (Japanese Economic Review, 2012)
This note extends Matsuyama's 0–1 endogenous retirement choice model to the framework with continuous endogenous retirement choice to study the consumption‐saving decision and capital accumulation in an overlapping generation model. The conditions for the existence of multiple steady states have been derived. In contrast to the 0 or 1 labour choice, the partial retirement may be a stable steady state under the continuous endogenous retirement choice in the second period. And this implies that partial retirement may be a stable optimal choice. Also, we find that the retirement choice depends on the initial capital stock when there are multiple steady states.